2015
DOI: 10.1111/den.12475
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative abdominal collections drainage: Percutaneous versus guided by endoscopic ultrasound

Abstract: EUS-GD is as effective and safe as PD in patients with POFC. The advantage of not requiring external drainage and a trend to higher clinical success and lower total costs must be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
31
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 11 publications
3
31
0
Order By: Relevance
“…In this edition of the Journal, Téllez‐Ávila and colleagues report their experience comparing EUS and percutaneous techniques for drainage of PAFC . Two 7‐Fr double pigtail plastic stents were placed in the EUS group whereas either an 8.5‐ or a 10.2‐Fr drainage catheter was inserted in the percutaneous group with a follow‐up computed tomography (CT) scan obtained 6–8 weeks post‐procedure to assess treatment response.…”
mentioning
confidence: 56%
See 1 more Smart Citation
“…In this edition of the Journal, Téllez‐Ávila and colleagues report their experience comparing EUS and percutaneous techniques for drainage of PAFC . Two 7‐Fr double pigtail plastic stents were placed in the EUS group whereas either an 8.5‐ or a 10.2‐Fr drainage catheter was inserted in the percutaneous group with a follow‐up computed tomography (CT) scan obtained 6–8 weeks post‐procedure to assess treatment response.…”
mentioning
confidence: 56%
“…pancreatic duct or cystic duct leaks). Although the clinical symptoms may improve initially after internal transmural drainage as in the present study, the collections rarely resolve completely or they recur if there is active leak. In addition to internal stent placement, these patients require concomitant treatment such as transpapillary biliary or pancreatic duct stenting to divert the flow of secretions.…”
mentioning
confidence: 99%
“…Comparative retrospective studies between EUS-GD and PD for POFC in 2012 and 2013 found no significant differences in terms of technical and clinical success as well as recurrence rates between these procedures when performed in patients who had undergone partial pancreatic resections [31,32]. In the same manner, Téllez-Ávila and colleagues reported similar safety and efficacy outcomes including also patients with non-pancreatic surgical interventions [33]. No differences with respect to adverse events rates were noted.…”
Section: Discussionmentioning
confidence: 91%
“…Drain placement on the basis of our results seems not to protect from the formation of an abscess neither facilitate fistula or bleeding diagnosis of a fistula. Moreover, recent advances in interventional radiology as ultrasound-or computed tomography (CT)-guided percutaneous drainage and aspiration allowed surgeons to manage mininvasivelly the above mentioned complications with very low risk of intestinal injury (12,13).…”
Section: Discussionmentioning
confidence: 99%